Brazil nuts are subject to infection with B and G aflatoxin-producing fungus, Aspergillus pseudonomius - Massi, Fernanda Pelisson; Vieira, Maria Lúcia Carneiro; Sartori, Daniele; Penha, Rafael Elias Silva; de Freitas Munhoz, Carla; Ferreira, Josué Maldonado; Iamanaka, Beatriz Thie; Taniwaki, Marta Hiromi; Frisvad, Jens C.; Fungaro, Maria Helena Pelegrinelli (International journal of food microbiology, 2014)
The exploitation of the Brazil nut is one of the most important activities of the extractive communities of the Amazon rainforest. However, its commercialization can be affected by the presence of aflatoxins produced by fungi, namely Aspergillus section Flavi. In the present study, we investigated a collection of Aspergillus nomius strains isolated from Brazil nuts using different approaches, including morphological characters, RAPD and AFLP profiles, partial β-tubulin and calmodulin nucleotide sequences, aflatoxin patterns, as well as tolerance to low water activity in cultured media. Results showed that most of the isolates do belong to A. nomius species, but a few were re-identified as Aspergillus pseudonomius, a very recently described species. The results of the analyses of molecular variance, as well as the high pairwise FST values between A. nomius and A. pseudonomius suggested the isolation between these two species and the inexistence of gene flow. Fixed interspecific nucleotide polymorphisms at β-tubulin and calmodulin loci are presented. All A. pseudonomius strains analyzed produced aflatoxins AFB1, AFB2, AFG1 and AFG2. This study contains the first-ever report on the occurrence in Brazil nuts of A. pseudonomius. The G-type aflatoxins and the mycotoxin tenuazonic acid are reported here for the first time in A. pseudonomius. •Brazil nuts may harbor A. pseudonomius, a sibling species of A. nomius.•A. pseudonomius strains might be able to produce both B and G-type aflatoxins.•A. pseudonomius strains might be able to produce both B and G-type aflatoxins.•The mycotoxin tenuazonic acid is reported for the first time in A. pseudonomius.•The best way to distinguish these species is to analyze benA and cmd gene sequences.